Analisis Survei Kepuasan Pelanggan Terhadap Mutu Pelayanan Di Rumah Sakit Jiwa Tampan Provinsi Riau - Oktavia Dewi; Raviola Raviola; Nila Puspita Sari (Jurnal Kesehatan Komunitas, 2021)
Patient satisfaction is an important and commonly used indicator for measuring the quality in health care. Riau Province, Pekanbaru were the cities with high numbers of mental disorders. This study aims to know consumerâ€™s satisfaction with the quality service in Tampan Mental Health Hospital, Riau Province 2020. This research was a descriptive qualitative in terms of patient (family) satisfaction for health services in Mental Health Hospital Tampan, Riau Province. There were 100 samples collected by calculated the numbers of public satisfaction index using a questionnaire. The results showed that patient satisfaction of service quality in Mental Health Hospital Tampan, Riau Province classified as â€œAâ€ category (very good) and 87 point average. It conclude that costumerâ€™s satisfaction of service quality in Tampan Mental Health Hospital were very good.